Construction of Access Rules for Data Transaction Subjects - Simin Li (Law and Economy, 2024)
At present, data exchanges have been set up in various provinces and cities in China, but China has not yet established uniform rules for data transactions. As an important threshold to ensure the security of data transactions, it is of great significance to construct access rules for data transaction subject. By building access rules for data transaction subjects, data transaction rules will be gradually improved, which is also a positive response to China’s policy requirements. Adhering to the principle of ensuring data security and promoting the release of data value, this paper analyzes the existing rules of data exchanges and explores the construction ideas of access rules for data transaction subjects. Data transaction subjects can be divided into data providers and data demanders. In addition to examining the basic situation of the subject of the transaction, a more detailed examination is needed. For data providers, it is necessary to review whether they have any recent data-related violations and whether they have a sound data compliance management system. For data demanders, it is also necessary to review their data-related breaches, cybersecurity protection capabilities, and data security protection capabilities.